Communicative, scientific and pedagogical intentionality of the image: from the first illustrated book to interactive materials in the COVID-19 Post-pandemic - Quintero Corzo, Josefina; Munévar Quintero, Fabio Ignacio; Infante Castaño, Gloria Esperanza (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objectives: Explore the iconographic trends that have shaped the communicative, scientific and pedagogical uses and intentions of images and illustrations in school contexts, starting with the first didactic book published at the beginning of modernity, 17th century, until the implementation of virtual pedagogies during the COVID-19 pandemic period in the 21st century. Method: Historiographical documentary analysis of primary and secondary sources based on iconographic contents by periods and eras of change. Lessons, demos and interviews were conducted through virtual platforms enabled during school periods in times of pandemic and post-pandemic. Originality/contribution: The images and languages illustrated in printed and virtual educational materials constitute a significant historical testimony to communicate, interpret, read, decipher codes and learn in certain spaces, times and intentions. The first illustrated book designed at the beginning of modernity marked the genesis of active pedagogies in terms of learning the first letters. The use of images adapts to the possibilities of technological developments and stimulates the intellectual abilities of teachers and students in each era. Conclusions:  The incorporation of images in educational contexts is a contribution of active pedagogies. The thematic structure that makes up the iconic teaching materials in elementary schools expands to other curricular areas and to other advanced levels of the educational process. Images carry intentions that help stimulate scientific skills such as observing, imitating, discovering, ideating, representing objects and reconstructing situations in the natural context, while leading to the investigation and construction of concrete or abstract concepts. Currently, the contribution of images is evident given the profuse advancement of media resources, which are becoming essential for communities of the present and the future that learn in both spaces, face-to-face and virtual, just as happened in times of the pandemic caused by COVID-19.